KESADARAN PENGGUNA TERHADAP KEAMANAN PENYIMPANAN DATA DALAM CLOUD COMPUTING - Komalasari, Rita (TEMATIK, 2014)
Abstract : Cloud computing has changed the way an organization's approach to information technology (IT), enabling a company to become more agile, introducing a new business model, providing additional services and reduce IT financing. Cloud computing technology can be implemented in a variety of architectures, under the service and the application of different models, and can coexist with technology and other software design approach. But for professionals in the field of security, the cloud presents a major dilemma: How to embrace the benefits of cloud and maintain control over the security of the organization's assets? It becomes a question to determine whether the increased risk is proportional to the benefits provided.